Centrallyrik og interaktionslyrik i 00’erne - Larsen, Peter Stein (Passage - Tidsskrift for litteratur og kritik, 2010)
Peter Stein Larsen: “‘Centrallyrik’ and ‘Interaktionslyrik’ in the 00s” The aim of “‘Centrallyrik’ and ‘Interaktionslyrik’ in the 00s” is to examine two ways of understanding poetry in Denmark after the year 2000. The term ‘centrallyrik’ refers to texts with a monologic mode of enunciation and stylistic homogeneity. Furthermore, such texts possess a distinct autonomous quality. The antithesis to ‘centrallyrik’ I refer to as ‘interaktionslyrik’. Here, we are dealing with poetic texts in which the lyric speaker interacts with a number of social contexts. Works pertaining to this type of poetry do not possess the same level of autonomy as ‘centrallyrik’. Taking as my point of departure the concepts ‘centrallyrik’ and ‘interaktionslyrik’, I examine different trends and authorships in new Danish poetry. Finally, I discuss the future of new Danish poetry.